2020
DOI: 10.1038/s41598-020-73752-3
|View full text |Cite
|
Sign up to set email alerts
|

Spred2-deficiency enhances the proliferation of lung epithelial cells and alleviates pulmonary fibrosis induced by bleomycin

Abstract: The mitogen-activated protein kinase (MAPK) pathways are involved in many cellular processes, including the development of fibrosis. Here, we examined the role of Sprouty-related EVH-1-domain-containing protein (Spred) 2, a negative regulator of the MAPK-ERK pathway, in the development of bleomycin (BLM)-induced pulmonary fibrosis (PF). Compared to WT mice, Spred2−/− mice developed milder PF with increased proliferation of bronchial epithelial cells. Spred2−/− lung epithelial cells or MLE-12 cells treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Spred2 is a negative regulator of the MAPK–ERK pathway and is predominantly expressed in bronchial epithelial cells. In response to bleomycin, mice lacking Spred2 show increased proliferation of bronchial epithelial cells which may contribute to the observed milder fibrosis phenotype (Kawara et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Spred2 is a negative regulator of the MAPK–ERK pathway and is predominantly expressed in bronchial epithelial cells. In response to bleomycin, mice lacking Spred2 show increased proliferation of bronchial epithelial cells which may contribute to the observed milder fibrosis phenotype (Kawara et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Then, targeting the MEK pathway in fibrotic lung disease through the chemical inhibition of MEK prevented the progression of established lung fibrosis in the overexpressed TGF-α mouse model [58]. Recently, Kawara and collaborators demonstrated that Spred2 deficiency that represents an inhibitor of the rat sarcoma virus (Ras)/Rapidly Accelerated Fibrosarcoma (Raf)/MEK/ERK pathway involved in cell proliferation and inflammation, increasing the proliferation of lung epithelial cells, ameliorates pulmonary fibrosis induced by bleomycin [59]. Indeed, one of the most abundant heat shock proteins (HSPs), HSP90, that belongs to a large family of co-chaperones involved in the maintenance of proper cell protein homeostasis (proteostasis) [60], is increased in patients with IPF [61] and has recently been studied as both a biomarker of lung fibrosis and as a potential therapeutical target [62].…”
Section: Molecular and Cellular Key Players Behind Iipsmentioning
confidence: 99%
“…17 The SPRED2 was identified as a novel regulator of cardiac autophagy, and its deficiency could arouse cardiac dysfunction and life-threatening arrhythmias through impaired autophagy. [18][19][20] In addition, SPRED2 affected the development of lipopolysaccharide-induced lung inflammation by negatively regulating the ERK-MAPK pathway. 21 Since SPRED2 influences diabetesrelated diseases including insulin resistance, obesity, as well as inflammation, which plays a key role in DN, it may also participate in DN process.…”
Section: Introductionmentioning
confidence: 99%